Educational Journey on the Teachers' Narrative - Barbosa, Raquel Lazzari Leite [UNESP]; Annibal, Sérgio Fabiano [UNESP]; Nicácio, Rosemary Trabold [UNESP]; Boldarine, Rosária de Fátima [UNESP] (My University, 2014)
Initial and continuous education for teachers has been studied at Group of Studies and Research on Language, Teaching and Teachers’ narrative (GEPLENP in Portuguese). In order to do so, we use teacher’s narratives from public schools in Assis/SP. Narrative researches have been very widely spread either in Brazil or in any other country. Meaningful papers have shown how important the topic is as well as the method used. This research tries to identify teachers’ social representations, which result from historic, cultural and time constitutions in order to get close to group of teachers’ representations about their initial and continuous education. The individual and singular narrative method gives us the opportunity to access the history told by the participants. The results point out that initial education promotes the opposition between theory and praxis and use of tool is highlighted in continuous education, which limits possibilities of teachers’ reflection on their own school role thus evidencing institutional interests.
Keywords: Teacher education; Narratives; Social representations